In-Situ Assessment of Fracture in SiCf/SiC Under Computed X-Ray Tomography - Martin Bache (ASME Proceedings: Ceramics, 2018)
The use of X-ray computed tomography (XCT) for detecting sub-critical damage and ultimate failure mechanisms in a ceramic matrix composite is demonstrated. To this end, an initial XCT investigation of a CMC sample, using a commercially available in-situ mechanical loading rig, is presented. As an important step toward a better understanding of the mechanical behaviour of these materials, in-situ XCT inspection was performed on a macroscopic scaled test coupon, i.e. sampling a significant number of fibre bundles, whilst the material was subjected to monotonic tensile load. The observation of inherent processing artefacts, and the tracking of resultant damage in the structure of CMCs, was demonstrated, supported by post test inspections using optical and scanning electron microscopy. Further consideration is given to the requirements for developing XCT systems for in-situ inspection of CMC materials.